2015
DOI: 10.1177/0021998315602326
|View full text |Cite
|
Sign up to set email alerts
|

Shielding effectiveness of carbon-filled polypropylene composites

Abstract: Adding conductive carbon fillers to insulating thermoplastic resins increases composite shielding effectiveness. In this study, varying amounts of three different carbons (carbon black, synthetic graphite particles, and carbon nanotubes) were added to polypropylene resin. The resulting single filler composites were tested for shielding effectiveness. The effects of single fillers and combinations of two different carbon fillers were studied via a factorial design. At the highest single filler loadings, the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Table shows a comparison of EMI SE values of the PC with different carbon filler species and contents. Table also shows the EMI SE values of the PP/carbon black composite, polystyrene (PS)/graphite composite, epoxy/single wall CNT composite, and polyamide‐6 (PA‐6)/CF composite . From Table , the EMI SE values ranged from 14 to 26 dB with the carbon filler content from 3.0 to 15.0 wt %, and the EMI SE of the composite increased with the increase of filler proportion.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows a comparison of EMI SE values of the PC with different carbon filler species and contents. Table also shows the EMI SE values of the PP/carbon black composite, polystyrene (PS)/graphite composite, epoxy/single wall CNT composite, and polyamide‐6 (PA‐6)/CF composite . From Table , the EMI SE values ranged from 14 to 26 dB with the carbon filler content from 3.0 to 15.0 wt %, and the EMI SE of the composite increased with the increase of filler proportion.…”
Section: Resultsmentioning
confidence: 99%
“…However these performances result from a combination of reflection and absorption rather than pure absorption. Regarding polypropylene composites interesting properties were observed at 800 MHz in [45]. In [46] up to 15 dB shielding effectiveness was obtained with polypropylene loaded with carbon fibers.…”
Section: Introductionmentioning
confidence: 94%
“…In the studies of the PBT/ CF (30 wt %) composite, Hwang reported the EMI SE of 11.1 dB at the frequency of 1.1 GHz . In the polypropylene (PP)/carbon black (CB) (10 wt %) composite by King et al ., they showed the EMI SE of 23.4 dB at the frequency of 0.8 GHz. Maiti and Khatus reported the EMI SE of 21.6 dB for the polycarbonate (PC)/graphene (2.4 wt %)/MWCNT (1.6 wt %) composite.…”
Section: Introductionmentioning
confidence: 99%